Severity of in vivo corticospinal tract degeneration is associated with survival in amyotrophic lateral sclerosis: a longitudinal, multicohort study. (28th February 2023) - Ta, Daniel; Ishaque, Abdullah H.; Elamy, Adam; Anand, Tanushka; Wu, Andrew; Eurich, Dean T.; Luk, Collin; Yang, Yee Hong; Kalra, Sanjay
Abstract: Background and purpose: This study sought to evaluate the relationship of progressive corticospinal tract (CST) degeneration with survival in patients with amyotrophic lateral sclerosis (ALS). Methods: Forty‐one ALS patients and 42 healthy controls were prospectively recruited from the Canadian ALS Neuroimaging Consortium. Magnetic resonance imaging scanning and clinical evaluations were performed on participants at three serial visits with 4‐month intervals. Texture analysis was performed on T1‐weighted magnetic resonance imaging scans and the texture feature 'autocorrelation' was quantified. Whole‐brain group‐level comparisons were performed between patient subgroups. Linear mixed models were used to evaluate longitudinal progression. Region‐of‐interest and 3D voxel‐wise Cox proportional‐hazards regression models were constructed for survival prediction. For all survival analyses, a second independent cohort was used for model validation. Results: Autocorrelation of the bilateral CST was increased at baseline and progressively increased over time at a faster rate in ALS short survivors. Cox proportional‐hazards regression analyses revealed autocorrelation of the CST as a significant predictor of survival at 5 years follow‐up (hazard ratio 1.28, p = 0.005). Similarly, voxel‐wise whole‐brain survival analyses revealed that increased autocorrelation of the CST was associated with shorter survival. ALS patients stratified by median autocorrelation in the CST had significantly different survival times using the Kaplan–Meier curve and log‐rank tests ( χ 2 = 7.402, p = 0.007). Conclusions: Severity of cerebral degeneration is associated with survival in ALS. CST degeneration progresses faster in subgroups of patients with shorter survival. Neuroimaging holds promise as a tool to improve patient management and facilitation of clinical trials. Abstract : The clinical and biological heterogeneity in amyotrophic lateral sclerosis poses significant challenges in providing accurate prognoses to patients and their families. In this study, in vivo degeneration of the corticospinal tract was quantified using magnetic resonance imaging texture analysis. Greater degeneration within the corticospinal tract was associated with shorter survival, supporting the use of neuroimaging tools as prognostic markers.